A DIVERSIDADE DE GÊNERO EM MATERIAIS DIDÁTICOS DA DISCIPLINA DE ARTE - Domingos Filho, Doacir (2018)
This work offers pedagogical practice materials that supplement Arte e Interação (BOZZANO, FRENDA & GUSMÃO, 2013) and Por Toda Parte (FERRARI, LIBÂNEO, SARDO & FERRARI, 2013), the two Art textbooks that have been in use by public state schools of Paraná, Brazil, through the National Didactic Book Program (PNLD). The material features art practices for the secondary level, and has been developed to avoid the problem of poor representativeness of women artists and queer art in the textbooks. The bibliographical review covers Art History and cultural feminism references (ARCHER, 2012; PERROT, 2007), as well as queer theory (BUTLER, 2016) and Sociology (HALL, 2011; BOURDIEU, 2014), with an emphasis on issues of cultural identity, male domination, androcentrism and habitus. Charts and graphics illustrate the analysis of each textbook, showing the amount of women, male and queer artists, and also pointing out names that are mentioned in both textbooks. The materials have been organized in three modules, and given the need to narrow their scope, they comprise the following topics: 1) Women artists during the baroque period; 2) Women artists in surrealism; 3) Art and cultural diversity, with three themes: queer art; Rosana Paulino and black women in Art; Angélica Dass and cultural identity. These pedagogical propositions are meant as an aid for Art teachers to increase cultural diversity in the curriculum. An outline for development in class is provided, with selected contents that will supplement the analyzed books. The material also serves as a planning model, which can be adapted by the teacher in order to include other necessary themes of Art history and criticism.